2022
DOI: 10.1021/acs.jchemed.2c00037
|View full text |Cite
|
Sign up to set email alerts
|

Review of Hands-On Laboratory Experiments Employing Household Supplies

Abstract: The possibility of conducting laboratory experiments at home without using commercially available kits, which might also be overly expensive, seems to be a suitable approach for a distance chemistry laboratory. Thus, several hands-on experiments with household supplies have been developed aiming at fostering students' laboratory competencies, as in a face-to-face chemistry laboratory course. This paper presents a scoping review mapping this type of experiments and identifying their characteristics to guide che… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 72 publications
0
15
0
Order By: Relevance
“…Schedule changes such as later start times and less synchronous teaching typical of other schools in the Czech Republic were also confirmed in our sample grammar schools (Pavlas et al, 2021). Despite a significant number of studies describing the possibility of transferring a hands-on activity to a distance form suitable for the lockdown case (Salta et al, 2022), its frontal form prevailed in Czech schools during distance education (Pavlas et al, 2021). Our data showed that demonstration experiments, in particular, were used significantly less during distance education than for face-to-face instruction, despite the fact that the experiments were generally rated as useful and fun by teachers and students alike, and demonstrations could be made online.…”
Section: Discussionmentioning
confidence: 99%
“…Schedule changes such as later start times and less synchronous teaching typical of other schools in the Czech Republic were also confirmed in our sample grammar schools (Pavlas et al, 2021). Despite a significant number of studies describing the possibility of transferring a hands-on activity to a distance form suitable for the lockdown case (Salta et al, 2022), its frontal form prevailed in Czech schools during distance education (Pavlas et al, 2021). Our data showed that demonstration experiments, in particular, were used significantly less during distance education than for face-to-face instruction, despite the fact that the experiments were generally rated as useful and fun by teachers and students alike, and demonstrations could be made online.…”
Section: Discussionmentioning
confidence: 99%
“…In this manner, we aimed to promote the appropriation of information while cultivating the curiosity of students about science. For the design, we had to consider the fact that the participating students had limited access to educational laboratories and that they had weaknesses in regards to scientific background and to the development of scientific skills and critical thinking. , The design was based on the use of pedagogies focused on research . Each kit contained the materials listed in Table and a manual titled “Exploring the fun side of chemistry with Meyer-UIS”.…”
Section: Methodsmentioning
confidence: 99%
“…The delivery and costs of the kits were covered by the project to facilitate the participation of the students. We should remark that, in this case, the families of the participating students belong to a population that is considered economically vulnerable and in which local access to the materials included in the kits may be very limited, hence becoming costly . On the other hand, and fortunately, the young promoters involved in the project had extensive skills in hosting and moderating remote sessions and in using social networks for academic purposes.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations